ROLE OF SOME ISOLATED SOIL CULTURES ON REDUCTION OF HERBICIDE TRIFLURALIN - Erguven, Gokhan Onder; Bayhan, Hurrem (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2016)
The study is about the removal of herbicide Trifluralin as COD parameter and monitoring the population dynamic of isolated cultures. These cultures were isolated from soil samples taken from these areas for their identifications before the use of herbicide. Removal of Trifluralin was determined by microbiological degradation with these produced bacteria and fungi in liquid media. With these growing bacteria and fungi, removal rate by bioremediation method studies were carried out. In addition to biodegradation mechanism, with the measurements of the turbidity; the colony number of microorganisms is monitored with isolated bacteria and fungi species. The removal efficiency for Bacillus simplex was 95% and Clostridium tetani species was 86%, by the fungi Penicillium simplicissimum, and Metacordcyceps chlamydosporia species, were 59% and 80% respectively in five days. Bioremediation study results have shown differences with respect to species in liquid media. Degradation time of these herbicides in liquid culture media with isolated cultures varied between 5 min. and 135 min.
Keywords: Herbicide; population dynamic; bioremediation; Trifluralin; colony number; POLYMERASE-CHAIN-REACTION; BIODEGRADATION; Environmental Sciences & Ecology